The Impact of Store Atmosphere on Customer Loyalty through Perceived Quality and Satisfaction: An Evidence from Boutique Industry in Tarakan - Rafiq Idris; Marso Marso (Master of Management, School of Business and Management, Petra Christian University, 2022)
The increasingly competitive retail industry demands the ability of retailers to use appropriate marketing strategies to build customer loyalty and dominate the targeted market. This research aims to examine the relationship between strategic variables and the influence of these variables on the loyalty of boutique customers in Tarakan City. The research model tests the direct effect of store atmosphere on perceived quality, direct and indirect effects of store atmosphere on satisfaction, direct and indirect effects of store atmosphere on loyalty, direct effects of perceived quality on satisfaction, the direct effect and indirect effect of perceived quality on loyalty, and the direct effect of satisfaction on customer loyalty. One hundred seventy-six (176) respondents were used as samples and drawn by the accidental sampling method. The test results with SmartPLS show that this study's measurement model meets the convergent and discriminant validity. The results of the path analysis indicated that the nine hypotheses study are supported by the data. The store atmosphere positively affects perceived quality, customer satisfaction, and customer loyalty. The perceived quality has a positive effect on satisfaction, and loyalty. Furthermore, satisfaction has a positive and significant effect on loyalty. The role of perceived quality mediates the effect of store atmosphere on satisfaction, and satisfaction mediates the impact of store atmosphere on loyalty. The results of this study also reveal that the effect of store atmosphere on loyalty is not mediated by service quality. Thus, the results of this study are one of the empirical evidence that contributes to the development of customer loyalty theory and is useful as a basis for developing marketing strategies to increase boutique customer loyalty.